ASPEK HUKUM DALAM PENERAPAN PRINSIP FULL DISCLOSURE DI PASAR MODAL - Zaenah (Faculty of Law, University of Dr. Soetomo, 2017)
Public Offering, known as Initial Public Offer (IPO), as ameans of fund raising with investment model, which is used as a means of expanding the business or to strengthen the company's finances without relying on debt to other parties. On a broad scale, as in the consideration of the formation of Capital Market Law No. 8 of 1995, that capital market has a strategic position to support the achievement of the national development objectives of creating a fair and prosperous society through one of the capital market activities namely the Public Offering of shares as a source of financing business field and investment means for the community. The law has been covering and regulating all capital market activities to create legal certainty for all parties involved in the capital market, through the obligation to apply full disclousure principle for companies conducting their public offerings that have implications to the IPO’s legality. Procedures and legal aspects in the application of the full disclousure principle will be explained in this paper, and expected to be an useful knowledge for anyone who needs information about IPO.